Lithium supplement diaphragm and preparation method and application thereof
By using a lithium-replenishing separator containing a migratory bonding layer of nanometal tin in a lithium-ion battery, the safety hazards and insufficient performance of existing lithium-ion battery replenishing technology are solved, achieving a more efficient lithium-replenishing effect and a more efficient lithium-replenishing technology. Good battery performance.
Patent Information
- Application Number
- CN202411535797.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-21
AI Technical Summary
The existing lithium-ion battery lithium supplement technology has safety hazards, poor stability and industrialization problems, and the selection of lithium supplement materials and process complexity lead to insufficient battery performance.
A lithium-replenishing separator is used, which is composed of a base film layer, a ceramic film layer, a metallic lithium porous layer and a migratory bonding layer. The bonding layer contains nano-metal tin to form a migratory LixSn alloy, which improves the stability and stability of the lithium-replenishing layer. efficiency.
It improves the first Coulomb efficiency, energy density and cycle performance of lithium-ion batteries, avoids safety hazards caused by direct contact of lithium metal with air, and has a simple process and low cost.
Smart Images

Figure CN119340616A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a technology in the field of secondary batteries, in particular to a lithium-supplementing diaphragm, and its preparation method and application. Background Art
[0002] Without lithium replenishment, the initial coulombic efficiency of lithium-ion batteries is generally 80% to 85%. To improve the initial efficiency and performance of lithium-ion batteries, lithium replenishment is often required. Currently, common lithium replenishment methods include negative electrode replenishment and positive electrode replenishment.
[0003] Anode lithium replenishment solutions encompass a variety of technologies, including physical mixing of metallic lithium, vacuum winding lithium plating, self-discharge lithiation, chemical lithium replenishment, and electrochemical lithiation. However, these technologies are limited in practical application by battery manufacturing processes, such as the compatibility of metallic lithium with the production environment, common solvents, binders, air, and heat treatment processes. This poses significant challenges to the industrialization of negative electrode lithium replenishment technologies.
[0004] Positive electrode lithium replenishment usually adopts an electrochemical method. By adding lithium replenishment materials to the positive electrode materials of lithium-ion batteries, the lithium replenishment materials decompose and release active lithium during the battery charging process to compensate for the irreversible active lithium loss caused by the growth of the negative electrode SEI film. Compared with negative electrode lithium replenishment, positive electrode lithium replenishment has obvious advantages in terms of safety and process convenience. However, it also has some problems. For example, materials such as Li3N and Li2O have low decomposition potentials, but poor stability and easy gas production, posing a safety hazard to the battery; although materials such as Li5FeO4 and Li6CoO4 have high irreversible capacity and good environmental stability, their decomposition products will increase the electrode mass and the decomposition voltage is also high, which is incompatible with most positive electrode materials.
[0005] In order to solve the above problems in the prior art, the present invention is provided. Summary of the Invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a lithium-supplementing diaphragm, a preparation method and application thereof, which can make up for the deficiencies in the initial efficiency of lithium-ion batteries, improve battery performance, and avoid the defects of existing lithium-supplementing solutions.
[0007] The first aspect of the present invention relates to a lithium replenishing diaphragm, comprising a base film layer, a ceramic film layer, a lithium replenishing layer and a release protective layer stacked in sequence;
[0008] The lithium supplement layer includes a metal lithium porous layer and a transferable bonding layer, which is arranged between the metal lithium porous layer and the release protective layer; the transferable bonding layer contains nano-metal tin, which combines with the metal lithium in the metal lithium porous layer to generate transferable Li x Sn alloy.
[0009] In some specific embodiments, the base film layer is composed of any one of a polyethylene base film, a polyethylene non-woven base film, a polypropylene base film, a polypropylene non-woven base film, a polypropylene-polyethylene-polypropylene composite base film, and a polyimide base film. Preferably, the base film layer has a thickness of 5 to 20 μm and a porosity of 31% to 50%; for example, the thickness is 5 μm, 6 μm, 8 μm, 10 μm, 13 μm, 16 μm, 17 μm, 19 μm, 20 μm, etc., and the porosity is 32%, 35%, 37%, 40%, 42%, 45%, 46%, 48%, 49%, 50%, etc.
[0010] For some specific implementation plans, the ceramic membrane layer is formed by drying a ceramic slurry on a base membrane layer, which plays a protective role to prevent lithium dendrites generated during the cycle of the battery cell from piercing the separator; by weight, the ceramic membrane layer includes 90% to 98% ceramic powder and 2% to 10% binder, totaling 100%; for example, the weight proportion of the ceramic powder is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, etc.
[0011] Preferably, the thickness of the ceramic membrane layer is 1 to 6 μm and the porosity is 25% to 55%; for example, the thickness is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, etc., and the porosity is 25%, 30%, 35%, 40%, 45%, 50%, 55%, etc.
[0012] Preferably, the ceramic powder is at least one of alumina, zirconia, and boehmite; the binder is at least one of polytetrafluoroethylene, polyvinylidene fluoride, acrylic acid, sodium carboxymethyl cellulose, and polyvinyl alcohol; and the ceramic slurry includes a solvent, which is at least one of deionized water and NMP.
[0013] Preferably, the ceramic slurry is applied on the base film layer by brushing, roller coating, spraying, tape casting or the like.
[0014] There is a corresponding relationship between the lithium-supplementing material in the lithium-supplementing diaphragm and the battery performance. Too much lithium-supplementing material will cause the remaining unconverted lithium source to form "dead lithium", and gather at the negative electrode interface to hinder the diffusion and mass transfer of lithium ions, resulting in greater polarization of the battery and lithium precipitation, affecting the cycle performance and safety performance; too little lithium-supplementing material will lead to insufficient lithium replenishment depth, irreversible capacity will still exist in the negative electrode, and the initial efficiency will be low.
[0015] In the present invention, the thickness and porosity of the lithium metal porous layer determine the amount of lithium supplementation material. Preferably, the lithium metal porous layer has a thickness of 1 to 3 μm, a porosity of 31% to 50%, and an average lithium metal particle size of 10 to 100 nm. For example, the thickness is 1 μm, 2 μm, 3 μm, etc., the porosity is 35%, 40%, 45%, 50%, etc., and the average lithium metal particle size is 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0016] In addition, the thickness of the transferable bonding layer also affects the lithium replenishment effect. Too large a thickness will lead to increased internal resistance, poor interface contact effect, and insufficient lithium replenishment depth. Too small a thickness will lead to poor adhesion with the electrode during the formation process and poor water vapor isolation effect. In the present invention, the transferable bonding layer has a thickness of 1.2 to 5 μm, a porosity of 30% to 60%, and a surface density of 1 to 1.4 mg / cm 2 The surface density affects the porosity of the transferable bonding layer. The larger the surface density, the smaller the porosity. For example, the thickness is 1.2 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc., and the surface density is 1 mg / cm 2 , 1.1mg / cm 2 , 1.2mg / cm 2 , 1.3mg / cm 2 , 1.4mg / cm 2 etc.; its thickness is greater than the thickness of the metallic lithium porous layer to ensure that the lithium replenishing layer has a good lithium replenishing depth and bonding performance; further preferably, the thickness of the migratable bonding layer is 1.2 to 1.7 times the thickness of the metallic lithium porous layer, for example, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 times, etc.
[0017] In some specific embodiments, the migratable bonding layer is formed by solidifying a bonding layer solution; by weight, the bonding layer solution comprises 85% to 95% organic solvent, 2% to 5% binder, and 2% to 10% nano-metal tin, totaling 100%, with a mass solids content of 40% to 60%. For example, the weight percentage of the organic solvent is 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, etc., the weight percentage of the binder is 2%, 3%, 4%, 5%, etc., and the weight percentage of the nano-metal tin is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0018] Preferably, the organic solvent is at least one of NMP and acetone, the binder is at least one of PVDF and PMMA, the particle size of the nano-metal tin is 30 to 100 nm, for example, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc., and the purity is not less than 99.99%; Li metal and metal tin are combined to form Li x Sn alloy can protect the porous layer of metallic lithium to a certain extent, isolate the air as much as possible, and slow down the oxidation of metallic lithium.
[0019] Preferably, the binding layer solution is applied on the metallic lithium porous layer by brush coating, roller coating, spray coating, tape casting or the like.
[0020] For some specific implementation plans, the release protective layer uses a polymer film, which is attached to the migratable bonding layer without bubbles or pores between the two. On the one hand, the polymer film can protect the lithium replenishment diaphragm in the storage state to prevent the metallic lithium in the lithium replenishment layer from being oxidized and losing its activity in the air. On the other hand, during the use of the lithium replenishment diaphragm, that is, during the preparation of the full battery, the separation is smooth so that the lithium replenishment diaphragm and the negative electrode membrane can be effectively contacted.
[0021] Preferably, the polymer film is one of PP film, PET film and PE film, and has a thickness of 1 to 2 μm.
[0022] A second aspect of the present invention relates to a method for preparing the above-mentioned lithium supplementation separator, comprising the following steps:
[0023] Ceramic slurry is coated on one side of the base film layer, and a ceramic film layer is formed on the base film layer after drying and curing; then, under vacuum conditions, a metallic lithium porous layer is plated on the ceramic film layer by evaporation; then, under an inert gas atmosphere, a migratable bonding layer containing nano-metal tin is arranged on the metallic lithium porous layer, and finally, a release protective layer is covered on the migratable bonding layer.
[0024] The third aspect of the present invention relates to the use of the above-mentioned lithium supplementing diaphragm in a lithium ion battery. The release protective layer of the lithium supplementing diaphragm is removed and then laminated to a negative electrode membrane to produce a lithium ion battery.
[0025] Compared with the prior art, the present invention has the following technical effects:
[0026] 1) Before use, the lithium-ion battery diaphragm is protected by a release layer, which can prevent the metal lithium from being oxidized and deactivated, thus ensuring the quality stability of the lithium-ion battery diaphragm. When manufacturing lithium-ion batteries, the release layer of the lithium-ion battery diaphragm is removed, and the transferable bonding layer continues to play a protective role. During the hot pressing process of the lithium-ion battery, the polymer in the transferable bonding layer melts and fills the pores of the negative electrode membrane under high temperature and high pressure, making the lithium xSn, the metallic lithium porous layer and the negative electrode membrane fully contact and react, thereby improving the initial coulombic efficiency of the lithium-ion battery; and improving the energy density and cycle performance of the lithium-ion battery;
[0027] 2) Compared with the lithium replenishment process of existing mass-produced battery cells, this process avoids direct contact of lithium metal with air, is less likely to cause fire and explosion, and is highly safe;
[0028] 3) The preparation method is simple and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM electron microscope image of surface A of the lithium-supplementing separator in Example 1;
[0030] Figure 2 This is the SEM electron microscope image of the B surface of the lithium-supplementing separator in Example 1. DETAILED DESCRIPTION
[0031] The present invention will be described in detail below in conjunction with specific embodiments. Experimental methods without specific conditions specified in the examples were carried out according to conventional methods and conditions.
[0032] Example 1
[0033] This embodiment relates to the manufacture of a lithium battery, and the process is as follows.
[0034] A polyethylene base film with a thickness of 7 μm and a porosity of 40% was used as the base film layer.
[0035] 475 g of alumina ceramic powder with an average particle size of 10 nm, 25 g of polyvinylidene fluoride as a binder, and 500 g of deionized water as a solvent were mechanically stirred and mixed to prepare a ceramic slurry with a mass solid content of 50%.
[0036] 1 g of metallic lithium powder with an average particle size of 10 nm was used to prepare a metallic lithium porous layer.
[0037] Take 3g of PVDF and dissolve it in 97g of organic solvent NMP to obtain a solution with a mass solid content of 3%. Then add 5g of metal tin powder with a purity of 99.99% and an average particle size of 30nm, and mix evenly with a double planetary mixer to prepare a bonding layer solution with a mass solid content of 7.6%.
[0038] Ceramic slurry is applied on one side of the base membrane layer with a coating thickness of 2μm. The base membrane layer is then placed in a dehumidification workshop for 48 hours to allow the ceramic slurry to dry and solidify to form a ceramic membrane layer with a porosity of 40%.
[0039] The film was transferred to a vacuum environment, and metallic lithium was evaporated on the surface of the dried ceramic film layer to form a metallic lithium porous layer with a thickness of 1 μm and a porosity of 40%.
[0040] The mixture was then transferred to a nitrogen atmosphere and the bonding layer solution was coated on the metallic lithium porous layer using a roller coating process. The layer was then dried and solidified to form a transferable bonding layer with a surface density of 1 mg / cm 2 , porosity of 40%, thickness of 1.2μm; during the roller coating process, metallic lithium and metallic tin combine under mechanical force to form Li x Sn alloy;
[0041] Finally, a PET release film is covered on the transferable bonding layer as a release protective layer to obtain a lithium supplementing diaphragm. Figure 1 and Figure 2 The figure shows the SEM electron microscope image of the lithium-supplementing membrane. The pores on the uncoated side (side B) are uniform, retaining the channel for ion shuttle, and the coated side (side A) appears to be covered with PE polymer.
[0042] A lithium-ion battery was prepared using the aforementioned lithium-replenishing separator: the positive electrode film NCM811, the lithium-replenishing separator, and the silicon-carbon-graphite composite negative electrode film were aligned roll-to-roll and then wound into a bare cell. The base film layer of the lithium-replenishing separator was bonded to the positive electrode film, and the migratable bonding layer was bonded to the negative electrode film. During the winding process, the release layer of the lithium-replenishing separator was removed while unwinding. The bare cell was hot-pressed at 80°C and a pressure of 5 MPa for 120 seconds, then encased in an aluminum-plastic film casing. Liquid was then injected, and finally pressurized at 1.5 MPa. The first stage of formation was at 80°C, a current of 0.2°C, and a voltage of 3.5V. The second stage of formation was at 45°C, a current of 0.3°C, and a voltage of 4.0V, resulting in a full lithium-ion battery.
[0043] After testing, the battery's initial efficiency was 91.5%.
[0044] Example 2
[0045] The only difference from Example 1 is that the average particle size of the metal tin powder is 50 nm. After testing, the first efficiency of the battery is 88.2%.
[0046] Example 3
[0047] The only difference from Example 1 is that the average particle size of the metallic lithium powder is 30 nm. After testing, the initial efficiency of the battery is 88.3%.
[0048] Example 4
[0049] The only difference from Example 1 is that the formation process is a one-step formation, the temperature is 80° C., the current is 0.2 C, and the voltage is 4.0 V. After testing, the battery's initial efficiency is 89.1%.
[0050] Comparative Example 1
[0051] The only difference from Example 1 is that the surface density of the migratable bonding layer is 1.5 mg / cm 2After testing, the battery's initial efficiency was 84%.
[0052] Comparing Example 1 and Example 2, after increasing the particle size of the metal tin powder (30nm VS 50nm), the first efficiency of the battery is slightly reduced. This may be due to the excessive synthesis of Li x Sn caused;
[0053] Comparing Example 1 and Example 3, after increasing the particle size of the metal lithium powder (10nm vs. 30nm), the first efficiency of the battery also decreased, which may be because the increase in the particle size of the metal lithium is inhibited by the inhibition of the negative electrode lithium replenishment.
[0054] Comparing Example 1 and Example 4, it can be found that the formation temperature should be lowered in the later stage of formation. If the formation is carried out at a high temperature, the SEI film formed will not be dense enough, and the initial efficiency of the battery will be reduced.
[0055] By comparing Example 1 and Comparative Example 1, it can be found that if the density of the transferable bonding layer is too high and the porosity is reduced, the first efficiency of the battery will be significantly reduced.
[0056] It should be emphasized that the above are merely preferred embodiments of the present invention and do not constitute any form of limitation to the present invention. Any simple modifications, equivalent variations, and modifications made to the above embodiments based on the technical essence of the present invention remain within the scope of the technical solutions of the present invention. The purpose of providing comparative examples is to highlight the technical effects of the embodiments and does not constitute a representation that the technical solutions in the comparative examples are prior art.
Claims
1. A lithium supplementing diaphragm, characterized in that: It includes a base film layer, a ceramic film layer, a lithium supplement layer and a release protective layer which are stacked in sequence; The lithium supplement layer includes a metal lithium porous layer and a transferable bonding layer, wherein the transferable bonding layer is arranged between the metal lithium porous layer and the release protective layer; the transferable bonding layer contains nano-metal tin, which combines with the metal lithium in the metal lithium porous layer to generate transferable Li x Sn alloy.
2. The lithium supplementing diaphragm according to claim 1, characterized in that: The base film layer is composed of any one of a polyethylene base film, a polyethylene non-woven base film, a polypropylene base film, a polypropylene non-woven base film, a polypropylene-polyethylene-polypropylene composite base film, and a polyimide base film; preferably, the base film layer has a thickness of 5 to 20 μm and a porosity of 31% to 50%.
3. The lithium supplementing diaphragm according to claim 1, characterized in that: The ceramic membrane layer is formed by drying a ceramic slurry on a base membrane layer; by weight, the ceramic slurry includes 90% to 98% of ceramic powder and 2% to 10% of a binder, totaling 100%; preferably, the ceramic powder is at least one of alumina, zirconium oxide, and boehmite, and the binder is at least one of polytetrafluoroethylene, polyvinylidene fluoride, acrylic acid, sodium carboxymethyl cellulose, and polyvinyl alcohol; the solvent is at least one of deionized water and NMP; preferably, the thickness of the ceramic membrane layer is 1 to 6 μm and the porosity is 25% to 55%.
4. The lithium supplementing diaphragm according to claim 1, characterized in that: The metal lithium porous layer is made by vacuum evaporation method, with a thickness of 1 to 3 μm and a porosity of 31% to 50%.
5. The lithium supplementing diaphragm according to claim 1, characterized in that: The transferable bonding layer is formed by solidifying a bonding layer solution; by weight percentage, the bonding layer solution includes 85% to 95% of an organic solvent, 2% to 5% of a binder, and 2% to 10% of nano-metal tin, totaling 100%, and a mass solid content of 40% to 60%; preferably, the organic solvent is at least one of NMP and acetone, the binder is at least one of PVDF and PMMA, the particle size of the nano-metal tin is 30 to 100 nm, and the purity is not less than 99.99%.
6. The lithium supplementing diaphragm according to claim 1, characterized in that: The thickness of the transferable bonding layer is 1.2 to 1.7 times the thickness of the metal lithium porous layer; preferably, the thickness of the transferable bonding layer is 1.2 to 5 μm.
7. The lithium supplementing diaphragm according to claim 1, characterized in that: The surface density of the transferable bonding layer is 1 to 1.4 mg / cm 2 .
8. The lithium supplementing diaphragm according to claim 7, characterized in that: The release protective layer is made of a polymer film, and the polymer film is one of a PP film, a PET film, and a PE film; preferably, the thickness of the polymer film is 1 to 2 μm.
9. A method for preparing the lithium supplementing diaphragm according to any one of claims 1 to 8, characterized in that: The following steps are involved: Ceramic slurry is coated on one side of the base film layer, and a ceramic film layer is formed on the base film layer after drying and curing; then, a metal lithium porous layer is plated on the ceramic film layer by evaporation under vacuum conditions; then, a transferable bonding layer containing nano-metal tin is arranged on the metal lithium porous layer under an inert gas atmosphere, and finally a release protective layer is covered on the transferable bonding layer.
10. Use of the lithium supplementing diaphragm according to any one of claims 1 to 8 in a lithium ion battery, wherein the release protective layer of the lithium supplementing diaphragm is removed and then the diaphragm is laminated with a negative electrode film to prepare a lithium ion battery.